1991
DOI: 10.1093/nar/19.7.1413
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive site 4 of the human β globin locus control region

Abstract: The Locus Control Region (LCR) of the human beta globin gene domain is defined by four erythroid-specific DNasel hypersensitive sites (HSS) located upstream of this multigene cluster. The LCR confers copy number dependent high levels of erythroid specific expression to a linked transgene, independent of the site of integration. To assess the role of the individual hypersensitive sites of the LCR, we have localized HSS4 to a 280bp fragment that is functional both in murine erythroleukaemia (MEL) cells and in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
0
2

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 33 publications
5
105
0
2
Order By: Relevance
“…The tandem GATA sequences from the HS4 HSFE were used in the test construct. Factor binding to these sites has also been well characterized (21,24), and both elements are 6/6-bp matches of the consensus GATA-1-binding sequence (45). The spacing between the NF-E2-and GATAbinding elements was the same as in the HS4 HSFE (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The tandem GATA sequences from the HS4 HSFE were used in the test construct. Factor binding to these sites has also been well characterized (21,24), and both elements are 6/6-bp matches of the consensus GATA-1-binding sequence (45). The spacing between the NF-E2-and GATAbinding elements was the same as in the HS4 HSFE (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…These bands comigrate with the two bands seen with the wild-type tandem GATA sites from HS4. These bands are due to single and double occupancy of the two sites (21,24). Both gel shift bands are competed by 200-fold excess unlabeled self-and wild-type HS4 GATA sequences.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…We and others have previously shown that the activity of the LCR resides in these hypersensitive site (HS) regions and identified the core elements as 200-300 bp fragments [10][11][12][13][14]. There is strong evidence suggesting that each HS retains the essential properties of the LCR, although each site varies with regard to the level of transcriptional stimulation per gene and its developmental specificity [15,16].…”
Section: Introductionmentioning
confidence: 99%